"Vem ver, gente, esse samba como é": caminhos, olhares e escutas acerca do Samba de Aboio-Sergipe - Almeida, Luan Vinícius Carvalho de (2022)
The focus of this work is the Samba de Aboio Santa Bárbara, from Povoado Aguada, in the municipality of Carmópolis-SE. Samba is a celebration in honor of Santa Bárbara/Iansã and the liberation of the enslaved. The samba takes place only once a year, at the end of Holy Week and has a Nagô origin, which is perceived in the bath of stones that represent the Saint. Several baths are made on these stones, such as the bath with honey and palm oil, bath with herbs and bath with the blood of male animals. After the baths, Samba de Aboio takes place in front of Santa's house, located in Povoado Aguada. Having ethnoresearch as a methodological support (MACEDO, 2015), the field research carried out between 2016 and 2019 was of fundamental relevance for the elaboration of this work, which included consulting the collection of interviews, observation of almost all stages of the party, formal and informal conversations with Samba players. The plurality of voices of people who samba in this party makes up the body of this work. This research is based on the concepts and reflections on Samba de Aboio and ancestry (CALDERARO, SANTOS, SILVA, 2007; ASSIS, 2018; MARTINS, 2021), drums and musicality (ROCHA, 2020; SANTANA, 2020); black families (GONZALEZ; COLLINS; OYEWUMI) and Nagô peoples (SODRÉ; 1998, 2017; AMARAL, 2012). Through the paths trodden in the territory, listening to the voices of the people of Samba de Aboio and the looks that I cast on the party, I present as research results, a conglomeration of reflections that discusses several issues based on the issue of the party and popular cultures aphrodiasporic.